Intercurtural Komunikasi Bisnis - Alyssa Ayunda Ningtyas; Lula Khalishah Azka Ramadhani; Alsuci Qoniliyah; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
Intercultural communication (ICC) has become a critical competence in the context of an increasingly interconnected and multicultural global business environment. This study aims to analyze the evolution of ICC models in recent literature and to identify challenges and strategies in managing cross-cultural communication. Using a systematic literature review method, the study finds that contemporary ICC models have shifted from static, culture-based knowledge approaches toward frameworks that integrate dimensions of digital adaptability, sociopolitical awareness, and multilingual identity. This integration emphasizes competence as a dynamic process of meaning negotiation, with digital literacy and sensitivity to power structures serving as key foundations for success. Furthermore, the review reveals that the use of English as a lingua franca (ELF) and multicultural teamwork often face relational challenges such as power asymmetries, native-speakerism ideology, and conflicting expectations of collaboration. Interactional competence strategies, such as “bracketing” and “categorial work,” are shown to be effective in bridging perceptual differences and in constructing a shared “third space” for productive interaction. These findings highlight the need for a reflective, adaptive, and context-sensitive ICC approach to support effective communication and collaboration in global business settings.